1995
DOI: 10.1128/aem.61.3.877-882.1995
|View full text |Cite
|
Sign up to set email alerts
|

Long lag times and high velocities in the motility of natural assemblages of marine bacteria

Abstract: The motility characteristics of natural assemblages of coastal marine bacteria were examined. Initially, less than 10% of the bacteria were motile. A single addition of tryptic soy broth caused an increase in the motile fraction of cells but only after 7 to 12 h. Motility peaked at 15 to 30 h, when more than 80% of cells were motile. These results support the proposal that energy limits motility in the marine environment. Cell speeds changed more than an order of magnitude on timescales of milliseconds and hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 24 publications
3
60
0
Order By: Relevance
“…For example, the swarm-ring velocity decreases as the attractant concentration increases (Brenner et al, 1998). This is consistent with previous work (Mitchell et al, 1995). Four pathways leading to aggregation were found: (1) stable continuous expansion; (2) stable to a concentration threshold; (3) spontaneously unstable and (4) increasingly unstable.…”
Section: Collective Behavioursupporting
confidence: 92%
See 1 more Smart Citation
“…For example, the swarm-ring velocity decreases as the attractant concentration increases (Brenner et al, 1998). This is consistent with previous work (Mitchell et al, 1995). Four pathways leading to aggregation were found: (1) stable continuous expansion; (2) stable to a concentration threshold; (3) spontaneously unstable and (4) increasingly unstable.…”
Section: Collective Behavioursupporting
confidence: 92%
“…The hyperswimmer strains are believed to be defective (Millikan & Ruby, 2002), but the two distinct populations in the squid's symbiosis sacks might mean that the (Mitchell et al, 1995) and (e) freshwater bacteria (Mitchell et al, 1991). (f) Run and arc, steering or, more formally, helical klinotaxis, with the ideal gradient concentration a line/plane across the centre.…”
Section: Collective Behaviourmentioning
confidence: 99%
“…Nature has created efficient biomotors through millions of years of evolution and uses them in numerous biological processes and cellular activities. Some of these biological nanomotors move extremely fast relative to their size, with speeds exceeding 100 body lengths s −1 (bl s −1 ) 1–3. Inspired by the sophistication of nature biomotors and driven by pioneering contributions of Sen and Mallouk's team and Ozin's group,4–6 major efforts are currently being devoted to the design of efficient high‐speed synthetic micro‐/nanoscale motors that convert chemical energy into autonomous motion 7–16.…”
Section: Introductionmentioning
confidence: 99%
“…Although the difference between swimming and non-swimming cells is not clear, previous studies have reported a few mechanisms of motility regulation in bacteria. Motility in some species is regulated by environmental conditions [42][43][44], and the production of flagella can be regulated by a genetic switch [45]. Non-swimming cells were not stuck to chamber surfaces, as all cells migrated multiple cell lengths during the data acquisition period.…”
Section: Band Speed Is Not Correlated With Any Individual Strain Propmentioning
confidence: 99%
“…Although non-swimming cells would contribute to the shape and dynamics of chemotactic gradients, it seems reasonable that non-swimming cells would not strongly influence the band speed. Many studies have shown that fraction of motile bacterial cells is usually low (about 10%) in natural environment, and may vary a lot (5% to 70%) depending on environmental factors [12,42,44,46,47].…”
Section: Band Speed Is Not Correlated With Any Individual Strain Propmentioning
confidence: 99%